'Strictly Non-committal': British Economic Policy and the Commonwealth. Issue 5 (3rd September 2018) - Arens, Preston
ABSTRACT: In British economic thinking, the Commonwealth is often considered as a valuable trade network undergirded with familial connections, shared history, and common values. Such rhetoric has made a recent resurgence in post-Brexit Britain as Britain disengages with a European Union based economic bloc and searches for closer association with other economic groups, including the Commonwealth. This paper explores the historical dimensions of British economic policy towards the Commonwealth, particularly during the Depression of the 1930s and World Wars, when Commonwealth economic cooperation was at its closest. By examining the historical roots of British economic engagement with the Commonwealth, this article looks at how British policy shifted according to the strictures of domestic needs and colonial economics. The self-serving, yet negotiated nature of  such policies has echoes not only in today's rhetoric, but also in terms of imperial nostalgia, and the durability of colonial economic structures and theories in the recesses of the British 'official mind'.